An Assessment of Pb and Cu in Waters, Sediments, and Mud Crabs (Scylla serrata) from Mangrove Ecosystem Near Tanjung Api-Api Port Area, South Sumatra, Indonesia - Rozirwan; Aning Puji Saputri; Redho Yoga Nugroho; Nadila Nur Khotimah; Wike Ayu Eka Putri; Fauziyah; Anna Ida Sunaryo Purwiyanto (Science and Technology Indonesia, 2023)
Heavy metal pollution from anthropogenic activities can harm aquatic ecosystems. This study aims to determine the concentration of heavy metals (Pb and Cu) in waters, sediments, and mud crabs (Scylla serrata), and to analyze the relationship between environmental parameters and S. serrata consumed by humans. Samples were taken in the mangrove ecosystem around the Tanjung Api-Api port area in South Sumatra, Indonesia. Pb and Cu analysis used the Atomic Absorption Spectrophotometer (AAS). Pb and Cu linkages in waters, sediments, and S. serrata analyzed by SigmaPlot V12.5 and Principal Component Analysis (PCA) analyzed by XLSTAT 2022. The limit consumption of S. serrata was calculated using MWI (Maximum Weekly Intake) and MIT (Maximum Intake Tolerance). Based on the results, the heavy metal Pb in water was 0.1055 – 0.1322 mg.L-1, and Cu was not detected. Furthermore, Pb in sediments ranged from 7.0104 - 11.8186 mg.kg-1, Cu 3.7127 - 4.5347 mg.kg-1, and Pb in S. serrata ranged from 0.0001 - 0.0021 mg.kg-1, and Cu ranged from 0.03 – 0.0791 mg.kg-1. The concentration of heavy metals in water, sediment, and S. serrata had not exceeded the specified quality standard, except for Pb in water. The principal component analysis obtained F1 (44.35%), F2 (27.53%) and F3 (17.83%) groups. Based on MWI and MIT value, it showed high quality which concluded S. serrata was still safe for human consumption.